Guidance using bearing-only measurements with three beacons in the plane. (June 2016) - Trinh, Minh Hoang; Ko, Gwi-Han; Pham, Viet Hoang; Oh, Kwang-Kyo; Ahn, Hyo-Sung
Abstract: This paper proposes a bearing-only measurement based guidance algorithm for a mobile agent to navigate in a two-dimensional plane. Based on the bearing vectors and the subtended angles related to three stationary beacons, the proposed algorithm allows the agent to reach its desired location. We show that the agent reaches its desired location globally asymptotically based on Lyapunov stability theory. Under some assumptions, the agent is also proved to reach the desired location exponentially based on Lyapunov's indirect method. Simulations and actual experimental tests on quadrotor system are also provided to verify the effectiveness of the proposed algorithm in outdoor environment.